Effects of Chemical and Radiation Sterilisation on the Biological and Biomechanical Properties of Decellularised Porcine Peripheral Nerves - Holland, James D. R.; Webster, Georgina; Rooney, Paul; Wilshaw, Stacy-Paul; Jennings, Louise M.; Berry, Helen E. (Frontiers in Bioengineering and Biotechnology, 2021)
There is a clinical need for novel graft materials for the repair of peripheral nerve defects. A decellularisation process has been developed for porcine peripheral nerves, yielding a material with potentially significant advantages over other devices currently being used clinically (such as autografts and nerve guidance conduits). Grafts derived from xenogeneic tissues should undergo sterilisation prior to clinical use. It has been reported that sterilisation methods may adversely affect the properties of decellularised tissues, and therefore potentially negatively impact on the ability to promote tissue regeneration. In this study, decellularised nerves were produced and sterilised by treatment with 0.1% (v/v) PAA, gamma radiation (25–28 kGy) or E Beam (33–37 kGy). The effect of sterilisation on the decellularised nerves was determined by cytotoxicity testing, histological staining, hydroxyproline assays, uniaxial tensile testing, antibody labelling for collagen type IV, laminin and fibronectin in the basal lamina, and differential scanning calorimetry. This study concluded that decellularised nerves retained biocompatibility following sterilisation. However, sterilisation affected the mechanical properties (PAA, gamma radiation), endoneurial structure and basement membrane composition (PAA) of decellularised nerves. No such alterations were observed following E Beam treatment, suggesting that this method may be preferable for the sterilisation of decellularised porcine peripheral nerves.